John Neff on investing - Neff, John (John B.); Mintz, Steven L. (New York : John Wiley, 1999)
"John Neff has proven time and again over the past three decades that bucking the system can pay off big. During his illustrious career as a money manager, Neff flew in the face of conventional wisdom by consistently passing over the big growth stocks of the moment in favor of inexpensive, underperforming ones - and he usually won. During his thirty-one years as portfolio manager for Vanguard's Windsor and Gemini Funds, he beat the market twenty-two times, through every imaginable stock market climate, while posting a fifty-seven-fold increase in an initial stake. When Windsor closed its doors to new investors in 1985, it was the largest mutual fund in the United States."--Jacket.
"Now retired from mutual fund management, Neff is ready to share the investment strategies that earned him international recognition as the "investor's investor.""--BOOK JACKET. "Packed with solid advice and guidance for anyone who aspires to using Neff's unique brand of value investing, John Neff on Investing offers invaluable lessons on using price-earnings ratios as a yardstick, zeroing in on undervalued stocks, interpreting earnings histories, and anticipating new market climates."--Jacket.
Foreword -- Preface -- Prologue: Citi Saga -- My Road To Windsor -- Journey East -- Grubbing It Out -- Basic Training -- Banker's Hours -- Baptism by Fire -- Taking Command at Windsor -- Enduring Principles -- Elements of Style -- The Bargain Basement -- Care and Maintenance of a Low P /E Portfolio -- A Market Journal -- The Silly Season -- Four Yards and a Cloud of Dust -- The Right Stuff -- Good Guys Persevere -- Deja Vu -- Epilogue: Rivers and Markets.
Includes bibliographical references and index.
Keywords: Investment analysis; Investments; Investment analysis; Investments